Cardiopulmonary Parameters and Arterial Blood Gases During Etorphine-Medetomidine-Midazolam Immobilization in Free-Ranging Black Rhinoceroses (Diceros bicornis) Undergoing Electro-Ejaculation—A Preliminary Study - Meuffels, Janine; Lueders, Imke; Bertschinger, Henk; Luther-Binoir, Ilse; Pohlin, Friederike; Gerber, Leandri; Tindall, Brendan (Frontiers in Veterinary Science, 2021)
Conservation management interventions for the critically endangered black rhinoceros (Diceros bicornis) require immobilization, which offer opportunities for semen collection and cryopreservation to establish genetic reservoirs. In free-ranging rhinoceroses, a combination of the potent opioid etorphine and the tranquilizer azaperone is routinely used for chemical immobilization but is associated with muscle rigidity and severe cardiopulmonary changes. Additionally, azaperone inhibits semen emission. Seven free-ranging, male, sexually mature black rhinoceroses were immobilized with an alternative protocol consisting of 4.5 mg etorphine, 5 mg medetomidine, 50 mg midazolam and 2500 IU hyaluronidase delivered remotely by darting from a helicopter. During the immobilization, electro-ejaculation was performed with a portable electro-ejaculator and a species-specific rectal probe. Animals were observed for muscle tremors. Longitudinal changes in respiratory rate, heart rate and peripheral oxyhemoglobin saturation, measured at 5 minute intervals, were assessed using a general mixed model. Non-invasive oscillometric blood pressure and arterial blood gas variables were measured at first handling and before reversal and compared using the Wilcoxon rank sum test. All animals were successfully immobilized, showed no muscle tremors, presented with normal heart rates and lactate concentration (< 5 mmol/L), recovered uneventfully, but experienced acidemia, hypoxemia and hypercapnia. Induction time and total time in recumbency were 4.2 ± 0.41 and 38.4 ± 6.9 minutes, respectively. Electro-stimulation commenced after 11.7 ± 3.98 minutes and completed after 24.3 ± 6.65 minutes. Semen-rich fractions were successfully collected from six animals. Our observations indicate that etorphine-medetomidine-midazolam provides a promising immobilization protocol for free-ranging black rhinoceroses, that allows for successful electro-ejaculation.